An efficient low-cost method for sampling floral visitors on down-facing flowers - de Andrade, Helen Camila; Santos David-Silva, Maria Eduarda; Barros Muniz, David; Marinho, Lucas Cardoso (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
Angiosperm flowers have morphological attributes that influence their interaction with pollinators, one of which is floral orientation. Pendent (down-facing) flowers are considered a protective mechanism against the loss of floral resources, such as pollen, nectar, and resin. This study proposes a new method for collecting floral visitors in Clusia grandiflora (Clusiaceae), a resinous species with downward-facing flowers. The Entomological Rod method consists of using a light stem (such as a buriti petiole or bamboo) pierced in the middle with a 50 ml Falcon tube attached, allowing direct capture of insects in the flowers without the need for pruning or sudden movements. Tested in Lençóis Maranhenses National Park (Maranhão, Brazil), the low-cost method demonstrated ease of application in difficult-to-access down-facing flowers.
Keywords: Meliponini; Euglossini; Active search.; Entomological rod